Nanoparticle modified heavy anti-corrosion material as well as preparation method and application thereof

By modifying heavy anticorrosion materials in nanoparticles, using nanomaterials such as polyaniline nanofibers and graphene oxide, an efficient anticorrosion coating is formed, which solves the problem of low density of existing coatings in high salt spray and high humidity and heat environments. Achieve long-term high-performance corrosion-proof effect.

CN119192959APending Publication Date: 2024-12-27XI AN JIAOTONG UNIV

Patent Information

Application Number
CN202411697184.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing heavy anticorrosion coating materials are difficult to effectively block corrosion in high salt spray, high humidity and heat, and high Cl-erosion environments. The added inorganic sheet-like materials and oxidizing metal salts have poor affinity, resulting in low coating density and inability to Effectively improve barrier performance, which may cause heavy metal contamination.

Method used

Using nanoparticle modified heavy anticorrosion materials, composed of resin solution, polyaniline nanofibers, graphene oxide, carbon nanotubes, fillers and additives, polyaniline nanofibers are prepared by heteroelement terpolymer emulsion polymerization to form cores/ The shell structure cooperates to enhance the anti-corrosion and mechanical properties of the material, and improves the density and stability of the coating.

Benefits of technology

It has achieved a coating with excellent corrosion resistance in high salt spray, high humidity heat and high Cl-erosion environments. It has a salt spray resistance, acid resistance and alkali resistance of more than 10,000 hours, and has excellent mechanical properties and adhesion, which can be extended. service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119192959A_ABST
    Figure CN119192959A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coating preparation, and discloses a nanoparticle modified heavy anti-corrosion material as well as a preparation method and application thereof. The nano-particle modified heavy anti-corrosion material comprises the following components in percentage by weight: 60-80% of a component A, 10-25% of a component B and 10-30% of a first solvent, wherein the total percentage is 100%; the component A comprises the following components in percentage by weight: 45%-60% of a resin solution, 0.5%-5% of graphene oxide, 8%-20% of polyaniline nanofibers, 0.5%-5% of carbon nanotubes, 0.6%-40% of a filler, 0.3%-3% of an additive and 8%-12% of a cosolvent, and the total percentage is 100%; the component B comprises the following components in percentage by weight: 40-60% of polyamide and 40-60% of a second solvent, wherein the total percentage is 100%. The nano-particle modified heavy anti-corrosion material prepared by the invention has excellent salt mist resistance, acid resistance, alkali resistance, good adhesive force and impact resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coating preparation, and in particular to a nano-particle modified heavy-duty anti-corrosion material and a preparation method and application thereof. Background Art

[0002] Corrosion is a phenomenon in which materials are destroyed by the interaction with the surrounding environment. It is a spontaneous process. Corrosion is widely present in various environments such as the atmosphere, water and soil. Metal corrosion seriously affects production safety, causes huge waste of resources and economic losses, and even causes major social events such as casualties and environmental pollution. Heavy corrosion protection is a key technology to solve the above-mentioned corrosion problems. In the prior art, metal protection methods suitable for heavy corrosion environments include the use of corrosion inhibitors, electroplating of inert materials, passivation of metals to form a dense passivation film, cathodic protection and coating. From the actual use effect, corrosion inhibitors are easy to use but have low efficiency; electroplating of inert precious metals has good effects but high costs; cathodic protection is suitable for some specific environments; coating protection is convenient and simple, so the most widely used metal protection method is to use heavy corrosion coating materials for heavy corrosion protection.

[0003] At present, the heavy-duty anti-corrosion coating materials used in the prior art mainly include epoxy heavy-duty anti-corrosion materials, acrylic heavy-duty anti-corrosion materials and fluororesin heavy-duty anti-corrosion materials. Among them, epoxy heavy-duty anti-corrosion materials have excellent impact resistance and toughness resistance, but poor weather resistance. Acrylic heavy-duty anti-corrosion materials are inexpensive, safe and environmentally friendly, have excellent aging resistance, good alkali resistance, and simple synthesis and processing, but are prone to flash corrosion and poor water resistance. Fluororesin heavy-duty anti-corrosion materials have high hardness, but high cost and difficult construction. It is difficult for the above-mentioned heavy-duty anti-corrosion coating materials to effectively protect the substrate.

[0004] In order to improve the barrier properties of the above-mentioned heavy-duty anti-corrosion coating materials, the existing technology usually adopts the method of adding flaky materials or / and oxidizing metal salts to the original coating components to improve the barrier properties of the coating. Among them, when inorganic flaky materials such as glass flakes, mica and basalt flakes are added, although the barrier properties of the coating can be improved to a certain extent, these inorganic flaky materials have poor affinity with the resin, and are prone to phase separation to form interface microcracks, resulting in micropores in the formed coating, and the coating density is low. It is difficult to effectively prevent corrosive media such as air, water and salt ions from entering the coating, causing metal corrosion, and it is impossible to effectively improve the barrier properties of the coating. The addition of oxidizing metal salts not only has the problem of poor affinity with the resin, resulting in micropores in the coating, low coating density, and difficulty in effectively improving the barrier properties of the coating; it may also cause heavy metal pollution, which in turn is harmful to human health. Summary of the invention

[0005] In order to solve the above technical problems, high salt fog, high humidity and heat, high Cl- The present invention provides a nanoparticle-modified heavy-duty anti-corrosion material and a preparation method and application thereof to meet the service requirements of a heavy-duty anti-corrosion environment such as erosion, strong scouring of oxygen-rich seawater, strong ultraviolet irradiation, alternating dry and wet erosion, and erosion by microorganisms and pollutants.

[0006] The nanoparticle-modified heavy-duty anticorrosive material and its preparation method and application are achieved through the following technical solutions: The invention provides a nano-particle modified heavy-duty anticorrosive material. The raw materials for preparing the nano-particle modified heavy-duty anticorrosive material consist of the following components in percentage by mass: 60% to 80% of component A, 10% to 25% of component B and 10% to 30% of a first solvent, which totals 100%.

[0007] The raw materials for preparing component A are composed of the following components in percentage by mass: Resin solution 45%~60%, graphene oxide 0.5%~5%, polyaniline nanofibers 8%~20%, carbon nanotubes 0.5%~5%, fillers 0.6%~40%, additives 0.3%~3% and co-solvents 8%~12%, totaling 100%.

[0008] The raw materials for preparing component B are composed of the following components in percentage by mass: Polyamide 40%~60% and second solvent 40%~60%, totaling 100%.

[0009] In the present invention, the polyaniline nanofibers are prepared by the following steps: A layer of polyaniline is coated on the surface of the nano metal oxide by adopting a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with the nano metal oxide as the core and the polyaniline as the shell, thereby obtaining the polyaniline nanofiber; wherein the nano metal oxide is one or more of CeO2, ZnO2, TiO2, Al2O3 and Fe2O3.

[0010] It should be noted that component A of the present invention is a heavy-duty anti-corrosion component with heavy-duty anti-corrosion performance to improve the corrosion resistance of the coating, and component B is mainly used as a curing component, so that component A and component B can be mixed to synergistically achieve the effect of the heavy-duty anti-corrosion material having excellent anti-corrosion performance while facilitating coating construction. The first solvent of the present invention is mainly used to adjust the viscosity of the material so that the prepared nanoparticle-modified heavy-duty anti-corrosion material can be sprayed on the surface of the material to be anti-corroded.

[0011] The present invention takes into account that although the polyaniline coating has a certain anti-corrosion effect, it has insufficient mechanical properties, extremely poor dispersibility and solubility, and is difficult to be used as a liquid coating with stable anti-corrosion performance. Therefore, in component A of the present invention, nano metal oxide is used as the core and polyaniline is used as the shell, and a heteroelement ternary copolymerization emulsion polymerization method is adopted to form polyaniline nanofibers with a core / shell structure, so that the nano metal oxide can achieve a modification effect on the polyaniline, so that the polyaniline nanofibers can undergo a reversible redox reaction, so that the polyaniline nanofibers can quickly gain and lose electrons between reversible redox states during the electrochemical corrosion process to promote the formation of a passivation oxide layer on the metal surface, which can hinder the transfer of corrosion charges, and thus effectively achieve an anti-corrosion effect. The present invention utilizes the catalyst effect of nano-doped modified polyaniline to produce a reversible redox reaction, hinder the transfer of corrosion charges, and greatly improve the anti-corrosion performance of the coating on the substrate material. Among them, the present invention uses one or more of CeO2, ZnO2, TiO2, Al2O3 and Fe2O3 as nano metal oxides, and prepares dispersed polyaniline nanofiber heavy-duty anti-corrosion materials through synergistic enhancement and modification of nano metal oxides and graphene oxide, which provides enhanced barrier properties and passivation protection for the composite material while having conductive and iron and magnetic properties, improving the mechanical properties, dispersibility and solubility of the material while greatly improving the anti-corrosion performance of the material.

[0012] It should be emphasized that the present invention takes Fe2O3 as the polyaniline nanofiber formed by the nano metal oxide as an example to further illustrate the principle of the passivation effect of the polyaniline nanofiber on the substrate used in the present invention. Figure 1 In a weakly acidic marine environment, the metal matrix generally undergoes oxygen absorption corrosion, and in a strong acidic environment, hydrogen evolution corrosion. At the same time, the ocean is rich in a large amount of Cl - Salt ions such as Cl can also corrode equipment. - The impact on metal corrosion is manifested in two aspects: first, it reduces the possibility of passive film formation on the surface of the material or accelerates the destruction of the passive film, thereby promoting local corrosion; second, it reduces the solubility of CO2 in aqueous solution, thereby alleviating the corrosion of the material. - It is not only enriched in the pits, but also accumulates in the areas without pits, reflecting that the double electrical layer structure at the interface between the matrix iron and the corrosion product film preferentially adsorbs Cl - In some areas, Cl - Accumulation nucleation accelerates the anode dissolution, forms pits, and further increases the Cl - Concentration: Once the concentration exceeds the critical value, the anode metal will remain in an activated state and the pitting pits will continue to expand and deepen. Figure 1In the figure, LS is the fully reduced state of polyaniline, and ES is the intermediate state of polyaniline reduction and oxidation. Due to the formation of a dense interpenetrating conductive network structure, electrons move to the surface of the coating, and the redox reaction occurs on the outer surface of the coating rather than on the metal surface, so that the reaction and the metal are spatially separated, protecting the metal from corrosion. By utilizing the reversible properties of polyaniline between the oxidation and reduction states, the Fe 3+ OH generated during the oxidation of polyaniline - The reaction generates a dense iron oxide passivation layer, which achieves anti-corrosion effect while the polyaniline is not consumed, thus ensuring the long life of the material during service. The use of Fe2O3-PANI nanofibers and the metal surface to form a binary interface protective film greatly reduces the surface tension of the metal material, achieving surface modification of the material, making it difficult for harmful substances such as acids, alkalis, and salts to adhere to the surface, making the material surface resistant to corrosion by harmful substances such as acids, alkalis, and salts, achieving high-performance anti-rust and anti-corrosion functions.

[0013] In component A of the present invention, graphene oxide is compounded on the basis of polyaniline nanofibers, so as to utilize the carrier capacity and small size effect of graphene oxide to realize further modification of polyaniline nanofibers, so that graphene oxide is stably connected to polyaniline nanofibers, thereby realizing further improvement of the dispersibility of polyaniline nanofibers, and also being able to improve the coating porosity and improve corrosion resistance. In addition, the deposition of polyaniline and nano-metal oxide in polyaniline nanofibers can enhance the barrier performance, corrosion inhibition ability and mechanical properties of graphene oxide. Based on the above, the present invention, by compounding polyaniline nanofibers and graphene oxide, makes graphene oxide further modify polyaniline nanofibers during the preparation process, so that graphene oxide can significantly enhance the heavy anti-corrosion performance and mechanical properties of the material while improving the dispersibility of polyaniline nanofibers.

[0014] The invention takes into account that graphene oxide is prone to self-agglomeration, which will affect the modification effect of graphene oxide on polyaniline nanofibers, so in component A of the present invention, carbon nanotubes are further compounded on the basis of graphene oxide, and the two-dimensional planar structure of graphene and the one-dimensional tubular structure of carbon nanotubes have complementarity, and carbon nanotubes can be embedded between graphene sheets or distributed on the graphene surface to form a multi-scale composite material structure, and the carbon nanotubes in this structure can be distributed between graphene sheets by multi-dimensional staggered arrangement, thereby reducing the direct contact and stacking of graphene sheets, thereby enhancing the dispersibility of graphene oxide in resin solution, and then improving the modification effect of graphene oxide on polyaniline nanofibers. Carbon nanotubes also have high electrical conductivity, can work in synergy with polyaniline nanofibers, and then improve the passivation, shielding and electric field effect played by polyaniline nanofibers when metals are corroded, thereby improving the inhibitory effect on metal corrosion. Moreover, carbon nanotubes also have high strength and high corrosion resistance. Based on the presence of graphene oxide, carbon nanotubes can be evenly dispersed in the resin solution, so that the density of the coating can be further improved after adding carbon nanotubes, effectively preventing the penetration of corrosive media, thereby improving the anti-corrosion performance of the coating. In addition, carbon nanotubes also have good chemical stability and can resist the erosion of various chemical substances, thereby extending the service life of the heavy anti-corrosion material.

[0015] In some preferred embodiments of the present invention, the resin solution is prepared by mixing the resin and the third solvent in a mass ratio of 2 to 5: 1, so that the resin component is directly added in the form of a resin solution, so that other raw materials of component A of the present invention can be evenly dispersed in the resin solution under interaction. And the resin solution, as the main film-forming substance, can have a good bonding effect on other raw materials, not only can it have good adhesion to the matrix, but also can further improve the synergistic relationship between the various raw materials, which is conducive to forming a nanoparticle-modified heavy-duty anticorrosive material with uniform components, and improving the overall chemical stability of the nanoparticle-modified heavy-duty anticorrosive material. Among them, in some more preferred embodiments of the present invention, the third solvent used in the present invention is a mixed solution of xylene, cyclohexanone and n-butanol, so that it can form a resin solution with uniform components with the resin, so as to improve the bonding effect on other raw materials.

[0016] In some preferred embodiments of the present invention, the filler is one or more of talcum powder, calcined flour, lead powder and SiO2, so that the filler is added to form an organic-inorganic alternating structure with the polyaniline nanofibers, thereby improving the overall mechanical properties of the nanoparticle-modified heavy-duty anti-corrosion material, improving the overall defense of the nanoparticle-modified heavy-duty anti-corrosion material against external physical or chemical impacts, and thereby improving the protective life of the nanoparticle-modified heavy-duty anti-corrosion material of the present invention for the substrate when used as an anti-corrosion coating.

[0017] In some preferred embodiments of the present invention, the additive is one or both of a defoamer and a dispersant, so as to further improve the uniformity and stability of the nanoparticle-modified heavy-duty antiseptic material by adding additives. Among them, in some preferred embodiments of the present invention, the defoamer is one or both of fatty alcohol ethoxysiloxane and polyether siloxane. In some preferred embodiments of the present invention, the dispersant is one or more of polyvinyl alcohol, polyacrylic acid, polyurethane, methyl cellulose, and polypropylene alcohol.

[0018] In some preferred embodiments of the present invention, the first solvent is a mixed solution of xylene, cyclohexanone and n-butanol.

[0019] In some preferred embodiments of the present invention, the second solvent is one or more of xylene, cyclohexanone and n-butanol.

[0020] In some preferred embodiments of the present invention, the co-solvent is one or both of propylene glycol methyl ether and isopropanol, so as to improve the solubility of each preparation raw material in the resin solution.

[0021] In some preferred embodiments of the present invention, the resin is one or more of epoxy resin, alkyd resin, chlorinated olefin resin, acrylic resin, polyurethane, silicone resin, fluororesin, unsaturated polyester and vinyl ester; wherein the epoxy resin is any one or more of E12 epoxy resin to E54 epoxy resin.

[0022] In some preferred embodiments of the present invention, the graphene oxide used is graphene oxide nanosheets prepared by a modified Hummers method.

[0023] The present invention also provides a method for preparing the above-mentioned nanoparticle-modified heavy-duty anticorrosion material, comprising the following steps: Step 1, preparation of component A: According to the mass percentage component composition of the raw materials prepared by component A, the corresponding masses of resin solution, graphene oxide, polyaniline nanofibers, carbon nanotubes, fillers, additives and cosolvents are weighed respectively for use; the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, fillers, additives and cosolvents are dispersed in the weighed resin solution in sequence, stirred evenly, and a first mixture is obtained; the first mixture is ball-milled to obtain a second mixture; the second mixture with a fineness of <10 μm is collected to obtain component A.

[0024] Step 2, preparation of component B: According to the mass percentage composition of the raw materials for preparing component B, corresponding masses of polyamide and the second solvent are weighed respectively for use; the weighed polyamide is evenly dispersed in the second solvent to obtain component B.

[0025] Step 3, weigh component A, component B and the first solvent: According to the mass percentage component composition of the raw materials for preparing the nanoparticle-modified heavy-duty anticorrosive material, corresponding masses of component A, component B and the first solvent are weighed respectively.

[0026] Step 4, mix component A and component B: Component A is allowed to stand for treatment and then stirred and mixed with component B, and then the first solvent is added and stirred and mixed to obtain a third mixed material that is evenly mixed.

[0027] Step 5, let stand: After the third mixed material is left to stand for a static treatment, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

[0028] In some preferred embodiments of the present invention, the ball milling rate of the ball milling treatment is 1000rpm~1500rpm, and the ball milling time is 1.5~2.5h, so that the various preparation raw materials of the component A are evenly mixed through the ball milling treatment, and during the ball milling process, the carbon nanotubes and graphene oxide work synergistically to achieve the modification of the polyaniline nanofibers without destroying the complete structure of the components.

[0029] In some preferred embodiments of the present invention, when preparing the resin solution, the corresponding mass of the resin and the third solvent are weighed respectively according to a mass ratio of 2 to 5:1 between the resin and the third solvent, the weighed third solvent is heated to 80°C to 90°C, the resin is slowly added under stirring, the stirring is stopped after the mixture is evenly mixed, and the mixture is then condensed and refluxed at 60°C to 70°C for 1 hour to obtain a uniform and transparent resin solution.

[0030] In some preferred embodiments of the present invention, the graphene oxide used is prepared by the following steps: Graphite powder is added to sulfuric acid solution and stirred for 5 min to 10 min to obtain a mixed solution. Then sodium nitrate and permanganate are gradually added to the mixed solution, mixed and stirred evenly, and then a certain amount of deionized water is added to dilute. The obtained graphene oxide is washed 3 times, and the mixture of dilute hydrochloric acid, deionized water and graphene oxide is placed in a centrifuge and centrifuged at 3500 rpm to 4500 rpm for 2 min to 5 min to obtain graphene oxide nanosheets.

[0031] In some preferred embodiments of the present invention, the polyaniline nanofibers are prepared by the following steps: A layer of polyaniline is coated on the surface of the nano metal oxide by adopting a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with the nano metal oxide as the core and the polyaniline as the shell, thereby obtaining the polyaniline nanofiber; wherein the nano metal oxide is one or more of CeO2, ZnO2, TiO2, Al2O3 and Fe2O3.

[0032] The present invention also provides an application of the above-mentioned nanoparticle-modified heavy-duty anti-corrosion material in an anti-corrosion coating.

[0033] In some preferred embodiments of the present invention, the nanoparticle-modified heavy-duty anti-corrosion material is coated on the surface of the substrate to be anti-corroded by spraying, and after curing, an anti-corrosion coating is formed on the surface of the substrate to be anti-corroded.

[0034] In some preferred embodiments of the present invention, the thickness of the anti-corrosion coating formed on the surface of the substrate to be anti-corroded is 100 μm to 700 μm.

[0035] In some preferred embodiments of the present invention, the nanoparticles of the present invention are used to modify the heavy anti-corrosion material according to the following steps: 1) According to the requirements of SY / T 0407-2012, the anti-corrosion area shall be treated before painting to remove scale, rust and oil stains. After drying, it shall be sandblasted to Sa 2.5 level specified in GB 8923-88 or polished to St 2 level; the surface dust shall be removed by compressed air blowing or vacuum cleaning, and the surface dust shall not be lower than level 3 specified in ISO 8502-3; the surface anchor pattern depth shall be 40 μm-70 μm as specified in SY / T 0319-2021 or the "medium (G)" level specified in ISO 8503-2.

[0036] 2) Prepare the nanoparticle-modified heavy-duty anti-corrosion material according to the preparation method and use it within 3 hours after preparation to avoid curing of the paint due to long-term storage, which will affect the performance of the paint.

[0037] 3) Robot spraying, spray gun spraying, and brush painting are used according to the use environment conditions. Pre-coating is performed on corners, interfaces, dead corners and other easily corroded areas before construction. During the coating process, environmental control is required to obtain the best coating quality. Environmental control mainly includes temperature, relative humidity and dew point. During the coating and anti-corrosion coating curing process, the relative humidity of the air is required to be lower than 85%, and the substrate temperature must be higher than the dew point temperature by more than 3°C. Usually, the ambient temperature during construction must be greater than 10°C, and the surface temperature of the steel must not exceed 45°C, and it is advisable to control it at 15°C to 30°C.

[0038] In some preferred embodiments of the present invention, when the spraying method is used for construction, the coating is diluted to a fluid state with low viscosity by a solvent for easy spraying, and the spray gun speed is adjusted to ensure that the dry film thickness after one spraying is 50μm~80μm. After the surface is completely cured and hardened after one spraying, spraying is performed again, and this is repeated. According to different corrosive environments, the thickness of the anti-corrosion coating formed by the final spraying is controlled to be 100μm~700μm.

[0039] In some preferred embodiments of the present invention, when the brushing method is used for construction, wool brushes, pig hair brushes, roller brushes and other tools can be selected according to the construction environment. After brushing once, the dry film thickness is measured after the coating is completely cured, and the number of brushing times is determined based on the dry film thickness after a single brushing. The thickness of the anti-corrosion coating formed by the final brushing is controlled to be 100μm~700μm.

[0040] 4) After the construction is completed, measure the overall thickness of the anti-corrosion coating to ensure it meets the requirements, and inspect the anti-corrosion coating as a whole. If there are defects such as leaks, re-coat it in time. After leaving it in a shaded and ventilated place for 5 to 10 days, confirm that there are no defects on the surface of the anti-corrosion coating before putting it into use.

[0041] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses component A as a heavy anti-corrosion component, component B mainly as a curing component, and a first solvent as a viscosity regulator of the coating material, so that after component A and component B are mixed in the first solvent, a coating material with uniform component distribution can be formed, so that the various components of the present invention can synergistically achieve the excellent anti-corrosion performance of the heavy anti-corrosion material while facilitating coating construction, thereby ensuring that a dense coating can be formed after coating, and effectively achieving the improvement of the barrier performance of the coating.

[0042] Component A of the present invention is composed of resin solution, polyaniline nanofiber, graphene oxide, carbon nanotube, filler, additive and cosolvent. Among them, the resin solution is the main film-forming substance, which can have a good bonding effect on other preparation raw materials, not only can it have good adhesion to the substrate, but also can further improve the synergistic relationship between various preparation raw materials, which is conducive to forming a nanoparticle-modified heavy-duty anti-corrosion material with uniform components, and improving the overall chemical stability of the nanoparticle-modified heavy-duty anti-corrosion material. The polyaniline nanofiber is the main heavy anti-corrosion component, and the polyaniline nanofiber of the present invention uses nano metal oxide as the core and polyaniline as the shell, adopts a heteroelement ternary copolymerization emulsion polymerization method, realizes nano doping modification of polyaniline and forms polyaniline nanofiber with a core / shell structure, so that the nano metal oxide can achieve the modification effect on polyaniline, the polyaniline nanofiber can undergo a reversible redox reaction, and the polyaniline nanofiber can quickly gain and lose electrons between reversible redox states during the electrochemical corrosion process to promote the formation of a passivation oxide layer on the metal surface, which can hinder the transfer of corrosion charges, and thus can effectively achieve an anti-corrosion effect. The addition of graphene oxide can utilize the carrier capacity and small size effect of graphene oxide to modify polyaniline, so that graphene oxide is stably connected to the organic coating, improves the coating porosity, and improves the corrosion resistance. At the same time, the deposition of polyaniline and oxide CeO2 / ZnO2 / TiO2 / Al2O3 / Fe2O3 can enhance the barrier performance, corrosion inhibition ability and mechanical properties of graphene oxide, and improve the dispersibility of polyaniline through multiple composite synergy, while greatly enhancing the heavy anti-corrosion performance and mechanical properties of the material. The present invention uses one or more of CeO2, ZnO2, TiO2, Al2O3 and Fe2O3 as nano metal oxides, and prepares dispersed polyaniline nanofiber heavy anti-corrosion materials through synergistic enhancement and modification of nano metal oxides and graphene oxide, while providing enhanced barrier properties and passivation protection for the composite material, it has conductive and iron and magnetic properties, improves the mechanical properties, dispersibility and solubility of the material, and greatly improves the anti-corrosion performance of the material. The addition of carbon nanotubes can inhibit the stacking or self-agglomeration of graphene oxide, thereby enhancing the dispersibility of graphene oxide in the resin solution, and then improving the modification effect of graphene oxide on polyaniline nanofibers. Carbon nanotubes also have high electrical conductivity and can work synergistically with polyaniline nanofibers, thereby improving the passivation, shielding and electric field effects of polyaniline nanofibers during metal corrosion, thereby improving the inhibitory effect on metal corrosion. Moreover, carbon nanotubes also have high strength and high corrosion resistance. On the basis of the presence of graphene oxide, carbon nanotubes can be evenly dispersed in the resin solution, and then the density of the coating can be further improved after adding carbon nanotubes, effectively preventing the penetration of corrosive media, thereby improving the anti-corrosion performance of the coating. In addition, carbon nanotubes also have good chemical stability and can resist the erosion of various chemical substances, thereby extending the service life of the heavy-duty anti-corrosion material.The addition of fillers can form an organic-inorganic alternating structure with polyaniline nanofibers, thereby improving the overall mechanical properties of the nanoparticle-modified heavy-duty anticorrosion material, improving the overall defense of the nanoparticle-modified heavy-duty anticorrosion material against external physical or chemical impacts, and thereby increasing the protective life of the nanoparticle-modified heavy-duty anticorrosion material of the present invention as an anticorrosion coating for the substrate. The addition of additives can further improve the uniformity and stability of the nanoparticle-modified heavy-duty anticorrosion material.

[0043] The nanoparticle modified heavy-duty anticorrosion material of the present invention is suitable for high salt spray, high humidity and heat, high Cl - It has extremely excellent functional stability and heavy-duty anti-corrosion effect in environments with corrosion, strong ultraviolet radiation, and frequent alternation of dryness and wetness. Tests have shown that the nanoparticle-modified heavy-duty anti-corrosion material of the present invention has salt spray resistance, acid resistance, and alkali resistance of more than 10,000 hours. The nanoparticle-modified heavy-duty anti-corrosion material of the present invention also has excellent mechanical properties, strong adhesion on the surface of the substrate material to be anti-corroded, strong impact resistance, and excellent wear resistance and elongation at break.

[0044] The raw materials for preparing the nanoparticle-modified heavy-duty anti-corrosion material coating of the present invention are environmentally friendly, and the nanoparticle-modified heavy-duty anti-corrosion material coating of the present invention is convenient to construct, easy to use, and does not generate harmful gases during the construction process. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 It is a schematic diagram of the principle of the passivation effect of the polyaniline nanofibers in the nanoparticle-modified heavy-duty anti-corrosion material of the present invention on the substrate; Figure 1 In the figure, LS is the completely reduced state of polyaniline, and ES is the reduction-oxidation intermediate state of polyaniline.

[0046] Figure 2 The present invention is a flow chart of the preparation process of the nanoparticle-modified heavy-duty anti-corrosion material.

[0047] Figure 3 The present invention is a photograph of component A, component B and a first solvent prepared in Example 1; wherein (a) is a photograph of component A prepared in Example 1, (b) is a photograph of component B prepared in Example 1, and (c) is a photograph of the first solvent prepared in Example 1.

[0048] Figure 4 The macroscopic morphology of the stainless steel plate before and after coating with the nanoparticle-modified heavy-duty anti-corrosion material of Example 1; wherein (a) is a photograph of the stainless steel plate before coating with the nanoparticle-modified heavy-duty anti-corrosion material of Example 1, and (b) is a photograph of the stainless steel plate after coating with the nanoparticle-modified heavy-duty anti-corrosion material of Example 1. DETAILED DESCRIPTION

[0049] The technical solutions in the embodiments of the present invention are described clearly and completely below. It should be noted that in the following embodiments of the present invention, the graphene oxide nanosheets used are prepared by the following steps:

[0050] Under ice-water bath conditions, graphite powder was added to concentrated sulfuric acid and stirred for 10 minutes to mix evenly, and then sodium nitrate and oxidant potassium permanganate were added in sequence, and stirring was continued for 45 minutes, and then stirring was continued for 2 hours in a 35°C water bath to obtain a mixed solution. Deionized water was slowly added to the obtained mixed solution and stirred continuously for 15 minutes, then the system temperature was raised to 98°C, stirred for 60 minutes, and then cooled to 55°C, and 30% volume fraction of hydrogen peroxide was added until the solution turned bright yellow to obtain a reaction solution. The reaction solution was filtered while hot and washed with dilute hydrochloric acid to remove excess metal ions, and then repeatedly washed with deionized water until neutral, placed in a centrifuge and centrifuged at 4000rpm for 5 minutes to obtain graphene oxide nanosheets. Among them, the mass ratio of graphite to sodium nitrate and potassium permanganate was 2:2:6, and the amount ratio of graphite to concentrated sulfuric acid was 2g:100mL.

[0051] It should also be noted that in the following embodiments of the present invention, when the polyaniline nanofibers are prepared by using the heteroelement ternary copolymerization emulsion polymerization method, they are prepared by the following steps: 1) Ultrasonic cleaning of nano-metal oxide fibers was performed twice, each time for 15 min.

[0052] 2) Place the nano-metal oxide fibers after ultrasonic cleaning in a vacuum drying oven, dry them at 60°C for 3 h, then take them out for later use.

[0053] 3) Using sodium dodecyl sulfate as an emulsifier, the dried oxide, sodium dodecyl sulfate, aniline and a 0.1 mol / L hydrochloric acid solution were added into a three-necked flask in a mass ratio of 1:3:1:9, and magnetically stirred at 20°C for 30 min to obtain a mixed solution.

[0054] 4) Mix ammonium persulfate and 0.1 mol / L hydrochloric acid solution in a mass ratio of 21:9 to obtain an initiator.

[0055] 5) The initiator obtained in step 4) is added dropwise to the mixed solution in step 3). After the addition is complete, the reaction is continued at 20°C for 2 h. It can be observed that the solution is milky white at first, and after the addition of the initiator, the solution gradually turns dark green.

[0056] 6) After the reaction in step 5) is completed, the product is taken out, washed with deionized water and ethanol, and dried in a vacuum drying oven at 60° C. for 12 h to obtain the corresponding polyaniline nanofibers in each embodiment.

[0057] It should be noted that the nano-metal oxide fibers in the above step 1) can be replaced with the nano-metal oxide fibers actually used in various embodiments.

[0058] Example 1 See also Figure 2 This embodiment provides a nanoparticle-modified heavy-duty anticorrosion material, which is prepared by the following steps: Step 1, preparation of component A: 1.1) Xylene, cyclohexanone and n-butanol were mixed at a mass percentage of 76%, 12% and 12% to obtain a third solvent. According to the mass ratio of E44 epoxy resin to the third solvent of 4:1, the corresponding mass of E44 epoxy resin and the third solvent were weighed respectively, and the weighed third solvent was added to a container and heated and stirred to 80°C, and then the weighed E44 epoxy was slowly added and continuously stirred, and then the heating was stopped and condensed and refluxed for 1 hour to prepare a uniform and transparent resin solution.

[0059] 1.2) According to the above method, Fe2O3 is used as nano metal oxide, and a layer of polyaniline is coated on the surface of Fe2O3 by a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with Fe2O3 as the core and polyaniline as the shell, thereby obtaining the polyaniline nanofibers.

[0060] 1.3) According to the mass percentage composition of the raw materials prepared in component A below, weigh the corresponding mass of each raw material for use: 50% resin solution, 2% graphene oxide, 10% polyaniline nanofibers, 1% carbon nanotubes, 8% talcum powder, 8% dabai powder, 8% lithopone, 1.2% SiO2, 0.9% defoamer, 0.9% dispersant, and 10% cosolvent. In this embodiment, polyether siloxane is used as a defoamer, polyurethane is used as a dispersant, and isopropyl alcohol is used as a cosolvent.

[0061] 1.4) Disperse the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, talcum powder, calcined white powder, lithopone, SiO2, polyether siloxane, polyurethane and isopropyl alcohol in the weighed resin solution in sequence, stir evenly, and obtain a first mixture.

[0062] 1.5) The first mixed material is ball-milled to obtain a second mixed material; the second mixed material with a fineness of <10 μm is collected to obtain component A, and the obtained component A is shown in the following figure: Figure 3 As shown in Figure (a).

[0063] Step 2, preparation of component B: 2.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a second solvent: 76% xylene, 12% cyclohexanone and 12% n-butanol.

[0064] 2.2) The mass percentage composition of the raw materials prepared by component B is as follows: polyamide 55% and the second solvent 45% are weighed and set aside.

[0065] 2.3) The weighed polyamide is evenly dispersed in the second solvent to obtain component B, and the obtained component A is shown in the following figure. Figure 3 As shown in Figure (b).

[0066] Step 3, weigh component A, component B and the first solvent: 3.1) According to the following mass percentage composition, weigh the corresponding mass of xylene, cyclohexanone and n-butanol and mix them to obtain the first solvent: xylene 76%, cyclohexanone 12% and n-butanol 12%. The photo of the obtained first solvent is as follows Figure 3 As shown in Figure (c).

[0067] 3.2) According to the following mass percentage component composition of the raw material for preparing the nanoparticle modified heavy-duty anticorrosive material, the corresponding masses of component A, component B and the first solvent are weighed respectively: component A 70%, component B 15% and the first solvent 15%.

[0068] Step 4, mix component A and component B: The weighed component A was allowed to stand for 5 minutes, then stirred with the component B for 8 minutes to mix evenly, and then the first solvent was added and stirred for another 2 minutes to obtain a third mixed material that was evenly mixed.

[0069] Step 5, let stand: After the third mixed material is left to stand for 30 minutes, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

[0070] Example 2 See also Figure 2 This embodiment provides a nanoparticle-modified heavy-duty anticorrosion material, which is prepared by the following steps: Step 1, preparation of component A: 1.1) Xylene, cyclohexanone and n-butanol were mixed at a mass percentage of 76%, 12% and 12% to obtain a third solvent. According to the mass ratio of E44 epoxy resin to the third solvent of 4:1, the corresponding mass of E44 epoxy resin and the third solvent were weighed respectively, and the weighed third solvent was added to a container and heated and stirred to 80°C, and then the weighed E44 epoxy was slowly added and continuously stirred, and then the heating was stopped and condensed and refluxed for 1 hour to prepare a uniform and transparent resin solution.

[0071] 1.2) According to the above method, Fe2O3 is used as nano metal oxide, and a layer of polyaniline is coated on the surface of Fe2O3 by a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with Fe2O3 as the core and polyaniline as the shell, thereby obtaining the polyaniline nanofibers.

[0072] 1.3) According to the mass percentage composition of the raw materials prepared in component A below, weigh the corresponding mass of each raw material for use: resin solution 45%, graphene oxide 2%, polyaniline nanofiber 10%, carbon nanotube 1%, talcum powder 10%, white powder 10%, lead powder 10%, SiO2 1.2%, defoamer 0.9%, dispersant 0.9%, cosolvent 9%. In this embodiment, polyether siloxane is used as the defoamer, polyurethane is used as the dispersant, and isopropyl alcohol is used as the cosolvent.

[0073] 1.4) Disperse the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, talcum powder, calcined white powder, lithopone, SiO2, polyether siloxane, polyvinyl alcohol and isopropyl alcohol in the weighed resin solution in sequence, stir evenly, and obtain a first mixture.

[0074] 1.5) The first mixture is ball-milled to obtain a second mixture; the second mixture with a fineness of less than 10 μm is collected to obtain component A.

[0075] Step 2, preparation of component B: 2.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a second solvent: 76% xylene, 12% cyclohexanone and 12% n-butanol.

[0076] 2.2) The mass percentage composition of the raw materials prepared by component B is as follows: polyamide 55% and the second solvent 45% are weighed and set aside.

[0077] 2.3) The weighed polyamide is evenly dispersed in the second solvent to obtain component B.

[0078] Step 3, weigh component A, component B and the first solvent: 3.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a first solvent: 76% of xylene, 12% of cyclohexanone and 12% of n-butanol.

[0079] 3.2) According to the following mass percentage component composition of the raw material for preparing the nanoparticle modified heavy-duty anticorrosive material, the corresponding masses of component A, component B and the first solvent are weighed respectively: component A 70%, component B 15% and the first solvent 15%.

[0080] Step 4, mix component A and component B: The weighed component A was allowed to stand for 5 minutes, then stirred with the component B for 8 minutes to mix evenly, and then the first solvent was added and stirred for another 2 minutes to obtain a third mixed material that was evenly mixed.

[0081] Step 5, let stand: After the third mixed material is left to stand for 30 minutes, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

[0082] Example 3 See also Figure 2 This embodiment provides a nanoparticle-modified heavy-duty anticorrosion material, which is prepared by the following steps: Step 1, preparation of component A: 1.1) Xylene, cyclohexanone and n-butanol were mixed at a mass percentage of 76%, 12% and 12% to obtain a third solvent. According to the mass ratio of E44 epoxy resin to the third solvent of 3:1, the corresponding mass of E44 epoxy resin and the third solvent were weighed respectively, and the weighed third solvent was added to a container and heated and stirred to 80°C, and then the weighed E44 epoxy was slowly added and stirred continuously, and then the heating was stopped and condensed and refluxed for 1 hour to prepare a uniform and transparent resin solution.

[0083] 1.2) According to the above method, Fe2O3 is used as nano metal oxide, and a layer of polyaniline is coated on the surface of Fe2O3 by a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with Fe2O3 as the core and polyaniline as the shell, thereby obtaining the polyaniline nanofibers.

[0084] 1.3) Prepare the raw material composition according to the mass percentage of component A below, and weigh the corresponding mass of resin solution, graphene oxide, polyaniline nanofiber, carbon nanotube, filler, additive and cosolvent respectively for use: 55% resin solution, 2% graphene oxide, 10% polyaniline nanofiber, 1% carbon nanotube, 7% talcum powder, 7% dabai powder, 7% lithopone, 1.2% SiO2, 0.9% defoamer, 0.9% dispersant and 8% cosolvent. In this embodiment, fatty alcohol ethoxysiloxane is used as a defoamer, polyvinyl alcohol is used as a dispersant, and isopropyl alcohol is used as a cosolvent.

[0085] 1.4) Disperse the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, talcum powder, dabai powder, lithopone, SiO2, fatty alcohol ethoxysiloxane, polyvinyl alcohol and isopropanol in the weighed resin solution in sequence, stir evenly, and obtain a first mixture.

[0086] 1.5) The first mixture is ball-milled to obtain a second mixture; the second mixture with a fineness of less than 10 μm is collected to obtain component A.

[0087] Step 2, preparation of component B: 2.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a second solvent: 76% xylene, 12% cyclohexanone and 12% n-butanol.

[0088] 2.2) The mass percentage composition of the raw material prepared by component B is as follows: polyamide 55% and the second solvent 45% are weighed respectively for use.

[0089] 2.3) The weighed polyamide is evenly dispersed in the second solvent to obtain component B.

[0090] Step 3, weigh component A, component B and the first solvent: 3.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a first solvent: 76% of xylene, 12% of cyclohexanone and 12% of n-butanol.

[0091] 3.2) According to the following mass percentage component composition of the raw material for preparing the nanoparticle modified heavy-duty anticorrosive material, the corresponding masses of component A, component B and the first solvent are weighed respectively: component A 70%, component B 15% and the first solvent 15%.

[0092] Step 4, mix component A and component B: The weighed component A was allowed to stand for 5 minutes, then stirred with the component B for 8 minutes to mix evenly, and then the first solvent was added and stirred for 2 minutes to mix evenly to obtain a third mixed material.

[0093] Step 5, let stand: After the third mixed material is left to stand for 30 minutes, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

[0094] Example 4 See also Figure 2 This embodiment provides a nanoparticle-modified heavy-duty anticorrosion material, which is prepared by the following steps: Step 1, preparation of component A: 1.1) Xylene, cyclohexanone and n-butanol were mixed at a mass percentage of 76%, 12% and 12% to obtain a third solvent. According to the mass ratio of E44 epoxy resin to the third solvent of 4:1, the corresponding mass of E44 epoxy resin and the third solvent were weighed respectively, and the weighed third solvent was added to a container and heated and stirred to 80°C, and then the weighed E44 epoxy was slowly added and continuously stirred, and then the heating was stopped and condensed and refluxed for 1 hour to prepare a uniform and transparent resin solution.

[0095] 1.2) According to the above method, Al2O3 is used as nano metal oxide, and a layer of polyaniline is coated on the surface of Al2O3 by a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with Al2O3 as the core and polyaniline as the shell, thereby obtaining the polyaniline nanofibers.

[0096] 1.3) Prepare the raw material composition according to the mass percentage of component A below, and weigh the corresponding mass of resin solution, graphene oxide, polyaniline nanofiber, carbon nanotube, filler, additive and cosolvent respectively for use: 50% resin solution, 2% graphene oxide, 10% polyaniline nanofiber, 1% carbon nanotube, 8% talcum powder, 8% white powder, 8% lithopone, 1.2% SiO2, 0.9% defoamer, 0.9% dispersant and 10% cosolvent. In this embodiment, polyether siloxane is used as a defoamer, methyl cellulose is used as a dispersant, and propylene glycol methyl ether is used as a cosolvent.

[0097] 1.4) Disperse the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, talcum powder, dabai powder, lithopone, SiO2, polyether siloxane, methyl cellulose and propylene glycol methyl ether in the weighed resin solution in sequence, stir evenly, and obtain a first mixture.

[0098] 1.5) The first mixture is ball-milled to obtain a second mixture; the second mixture with a fineness of less than 10 μm is collected to obtain component A.

[0099] Step 2, preparation of component B: 2.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a second solvent: 76% xylene, 12% cyclohexanone and 12% n-butanol.

[0100] 2.2) The mass percentage composition of the raw material prepared by component B is as follows: polyamide 55% and the second solvent 45% are weighed respectively for use.

[0101] 2.3) The weighed polyamide is evenly dispersed in the second solvent to obtain component B.

[0102] Step 3, weigh component A, component B and the first solvent: 3.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a first solvent: 76% of xylene, 12% of cyclohexanone and 12% of n-butanol.

[0103] 3.2) According to the following mass percentage component composition of the raw material for preparing the nanoparticle modified heavy-duty anticorrosive material, the corresponding masses of component A, component B and the first solvent are weighed respectively: component A 60%, component B 25% and the first solvent 15%.

[0104] Step 4, mix component A and component B: The weighed component A was allowed to stand for 5 minutes, then stirred with the component B for 8 minutes to mix evenly, and then the first solvent was added and stirred for 2 minutes to mix evenly to obtain a third mixed material.

[0105] Step 5, let stand: After the third mixed material is left to stand for 30 minutes, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

[0106] Example 5 See also Figure 2 This embodiment provides a nanoparticle-modified heavy-duty anticorrosion material, which is prepared by the following steps: Step 1, preparation of component A: 1.1) Xylene, cyclohexanone and n-butanol were mixed at a mass percentage of 76%, 12% and 12% to obtain a third solvent. According to the mass ratio of E44 epoxy resin to the third solvent of 5:1, the corresponding mass of E44 epoxy resin and the third solvent were weighed respectively, and the weighed third solvent was added to a container and heated and stirred to 80°C, and then the weighed E44 epoxy was slowly added and continuously stirred, and then the heating was stopped and condensed and refluxed for 1 hour to prepare a uniform and transparent resin solution.

[0107] 1.2) According to the above method, TiO2 is used as the nano metal oxide, and a layer of polyaniline is coated on the surface of TiO2 by a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with TiO2 as the core and polyaniline as the shell, thereby obtaining the polyaniline nanofibers.

[0108] 1.3) Prepare the raw material composition according to the mass percentage of component A below, and weigh the corresponding mass of resin solution, graphene oxide, polyaniline nanofiber, carbon nanotube, filler, additive and cosolvent respectively for use: 50% resin solution, 2% graphene oxide, 10% polyaniline nanofiber, 1% carbon nanotube, 8% talcum powder, 8% white powder, 8% lithopone, 1.2% SiO2, 0.9% defoamer, 0.9% dispersant and 10% cosolvent. In this embodiment, polyether siloxane is used as the defoamer, polyacrylic acid is used as the dispersant, and isopropyl alcohol is used as the cosolvent.

[0109] 1.4) Disperse the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, talcum powder, whiting, lithopone, SiO2, polyether siloxane, polyacrylic acid and isopropyl alcohol in the weighed resin solution in sequence, stir evenly, and obtain a first mixture.

[0110] 1.5) The first mixture is ball-milled to obtain a second mixture; the second mixture with a fineness of less than 10 μm is collected to obtain component A.

[0111] Step 2, preparation of component B: 2.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a second solvent: 76% xylene, 12% cyclohexanone and 12% n-butanol.

[0112] 2.2) The mass percentage composition of the raw materials prepared by component B is as follows: polyamide 55% and the second solvent 45% are weighed and set aside.

[0113] 2.3) The weighed polyamide is evenly dispersed in the second solvent to obtain component B.

[0114] Step 3, weigh component A, component B and the first solvent: 3.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a first solvent: 76% of xylene, 12% of cyclohexanone and 12% of n-butanol.

[0115] 3.2) According to the following mass percentage component composition of the raw material for preparing the nanoparticle modified heavy-duty anticorrosive material, the corresponding masses of component A, component B and the first solvent are weighed respectively: component A 80%, component B 10% and the first solvent 10%.

[0116] Step 4, mix component A and component B: The weighed component A was allowed to stand for 5 minutes, then stirred with the component B for 8 minutes to mix evenly, and then the first solvent was added and stirred for 2 minutes to mix evenly to obtain a third mixed material.

[0117] Step 5, let stand: After the third mixed material is left to stand for 30 minutes, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

[0118] Example 6 See also Figure 2 This embodiment provides a nanoparticle-modified heavy-duty anticorrosion material, which is prepared by the following steps: Step 1, preparation of component A: 1.1) Xylene, cyclohexanone and n-butanol were mixed at a mass percentage of 76%, 12% and 12% to obtain a third solvent. According to the mass ratio of E44 epoxy resin to the third solvent of 3:1, the corresponding mass of E44 epoxy resin and the third solvent were weighed respectively, and the weighed third solvent was added to a container and heated and stirred to 80°C, and then the weighed E44 epoxy was slowly added and stirred continuously, and then the heating was stopped and condensed and refluxed for 1 hour to prepare a uniform and transparent resin solution.

[0119] 1.2) According to the above method, ZnO2 is used as the nano metal oxide, and a layer of polyaniline is coated on the surface of ZnO2 by a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with ZnO2 as the core and polyaniline as the shell, thereby obtaining polyaniline nanofibers.

[0120] 1.3) Prepare the raw material composition according to the mass percentage of component A below, and weigh the corresponding mass of resin solution, graphene oxide, polyaniline nanofiber, carbon nanotube, filler, additive and cosolvent respectively for use: 50% resin solution, 2% graphene oxide, 10% polyaniline nanofiber, 1% carbon nanotube, 8% talcum powder, 8% white powder, 8% lithopone, 1.2% SiO2, 0.9% defoamer, 0.9% dispersant and 10% cosolvent. In this embodiment, fatty alcohol ethoxysiloxane is used as a defoamer, polypropylene alcohol is used as a dispersant, and propylene glycol is used as a cosolvent.

[0121] 1.4) Disperse the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, talcum powder, calcined white powder, lead powder, SiO2, polyether siloxane, polypropylene alcohol and propylene glycol methyl ether in the weighed resin solution in sequence, stir evenly, and obtain a first mixture.

[0122] 1.5) The first mixture is ball-milled to obtain a second mixture; the second mixture with a fineness of less than 10 μm is collected to obtain component A.

[0123] Step 2, preparation of component B: 2.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a second solvent: 76% xylene, 12% cyclohexanone and 12% n-butanol.

[0124] 2.2) The mass percentage composition of the raw materials prepared by component B is as follows: polyamide 55% and the second solvent 45% are weighed and set aside.

[0125] 2.3) The weighed polyamide is evenly dispersed in the second solvent to obtain component B.

[0126] Step 3, weigh component A, component B and the first solvent: 3.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a first solvent: 76% of xylene, 12% of cyclohexanone and 12% of n-butanol.

[0127] 3.2) According to the following mass percentage component composition of the raw material for preparing the nanoparticle modified heavy-duty anticorrosive material, the corresponding masses of component A, component B and the first solvent are weighed respectively: component A 60%, component B 10% and the first solvent 30%.

[0128] Step 4, mix component A and component B: The weighed component A was allowed to stand for 5 minutes, then stirred with the component B for 8 minutes to mix evenly, and then the first solvent was added and stirred for 2 minutes to mix evenly to obtain a third mixed material.

[0129] Step 5, let stand: After the third mixed material is left to stand for 30 minutes, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

[0130] Example 7 See also Figure 2 This embodiment provides a nanoparticle-modified heavy-duty anticorrosion material, which is prepared by the following steps: Step 1, preparation of component A: 1.1) Xylene, cyclohexanone and n-butanol were mixed at a mass percentage of 76%, 12% and 12% to obtain a third solvent. According to the mass ratio of E44 epoxy resin to the third solvent of 5:1, the corresponding mass of E44 epoxy resin and the third solvent were weighed respectively, and the weighed third solvent was added to a container and heated and stirred to 80°C, and then the weighed E44 epoxy was slowly added and continuously stirred, and then the heating was stopped and condensed and refluxed for 1 hour to prepare a uniform and transparent resin solution.

[0131] 1.2) According to the above method, CeO2 is used as the nano metal oxide, and a layer of polyaniline is coated on the surface of CeO2 by a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with CeO2 as the core and polyaniline as the shell, thereby obtaining the polyaniline nanofibers.

[0132] 1.3) Prepare the raw material composition according to the mass percentage of component A below, and weigh the corresponding mass of resin solution, graphene oxide, polyaniline nanofiber, carbon nanotube, filler, additive and cosolvent respectively for use: 50% resin solution, 2% graphene oxide, 10% polyaniline nanofiber, 1% carbon nanotube, 8% talcum powder, 8% dabai powder, 8% lithopone, 1.2% SiO2, 0.9% defoamer, 0.9% dispersant and 10% cosolvent. In this embodiment, fatty alcohol ethoxysiloxane is used as a defoamer, polyacrylic acid is used as a dispersant, and isopropyl alcohol is used as a cosolvent.

[0133] 1.4) Disperse the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, talcum powder, dabai powder, lithopone, SiO2, fatty alcohol ethoxysiloxane, polyacrylic acid and isopropyl alcohol in the weighed resin solution in sequence, stir evenly, and obtain a first mixture.

[0134] 1.5) The first mixture is ball-milled to obtain a second mixture; the second mixture with a fineness of less than 10 μm is collected to obtain component A.

[0135] Step 2, preparation of component B: 2.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a second solvent: 76% xylene, 12% cyclohexanone and 12% n-butanol.

[0136] 2.2) The mass percentage composition of the raw materials prepared by component B is as follows: polyamide 55% and the second solvent 45% are weighed and set aside.

[0137] 2.3) The weighed polyamide is evenly dispersed in the second solvent to obtain component B.

[0138] Step 3, weigh component A, component B and the first solvent: 3.1) According to the following mass percentage composition, weigh the corresponding masses of xylene, cyclohexanone and n-butanol and mix them to obtain a first solvent: 76% of xylene, 12% of cyclohexanone and 12% of n-butanol.

[0139] 3.2) According to the following mass percentage component composition of the raw material for preparing the nanoparticle modified heavy-duty anticorrosive material, the corresponding masses of component A, component B and the first solvent are weighed respectively: component A 70%, component B 20% and the first solvent 10%.

[0140] Step 4, mix component A and component B: The weighed component A was allowed to stand for 5 minutes, then stirred with the component B for 8 minutes to mix evenly, and then the first solvent was added and stirred for 2 minutes to mix evenly to obtain a third mixed material.

[0141] Step 5, let stand: After the third mixed material is left to stand for 30 minutes, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

[0142] Comparative Example 1 A polyaniline graphene nanocomposite anti-corrosion coating in the prior art CN 104910752 A is used as a comparative example.

[0143] The performance indicators of the anti-corrosion coating corresponding to this comparative example are shown in Table 1.

[0144] Table 1 Performance indicators of the anti-corrosion coating corresponding to Comparative Example 1

[0145] Comparative Example 2 The performance of a water-based polyaniline anti-corrosion coating in the prior art CN 102702920 A is used as a comparative example.

[0146] The performance indicators of the anti-corrosion coating corresponding to this comparative example are shown in Table 2.

[0147] Table 2 Performance indicators of the anti-corrosion coating corresponding to Comparative Example 2

[0148] Experimental Section The present invention uses the nanoparticle-modified heavy-duty anti-corrosion material of Examples 1 to 3 and sprays it on the surface of a stainless steel plate as the anti-corrosion material according to the following method: 1) According to the requirements of SY / T 0407-2012, the anti-corrosion area on the stainless steel plate shall be treated before painting to remove scale, rust and oil stains, and then sandblasted to Sa 2.5 level specified in GB 8923-88 after drying; the surface dust shall be removed by compressed air blowing or vacuum cleaning, and the surface dust shall not be lower than level 3 specified in ISO 8502-3; the surface anchor pattern depth shall be 40μm-70μm as specified in SY / T 0319-2021 or the "medium (G)" level specified in ISO 8503-2.

[0149] 2) Spray coating is performed by adding the nanoparticle-modified heavy-duty anti-corrosion materials of Examples 1 to 3 into the coating gun respectively before coating.

[0150] 3) During the coating process, environmental control is required to obtain the best coating quality. Environmental control mainly includes temperature, relative humidity and dew point. During the coating and anti-corrosion coating curing process, the relative humidity of the air is required to be lower than 85%, and the substrate temperature must be higher than the dew point temperature by more than 3°C. Usually, the ambient temperature during construction must be greater than 10°C, and the surface temperature of the steel must not exceed 45°C, and it is advisable to control it at 15°C to 30°C.

[0151] During the coating process, the spraying speed of the coating gun is controlled at 3m / s~5m / s, and one spraying includes 4 full and uniform spraying. After one spraying is completed, it is air-dried and cured in the backlight for 8 hours. After the anti-corrosion coating is completely cured, the anti-corrosion coating thickness is measured at 10 different locations using an anti-corrosion coating side thickness meter and recorded. The thickness of the anti-corrosion coating after one spraying should not be greater than 80μm.

[0152] 4) After the coating is completed, measure the overall thickness of the anti-corrosion coating to ensure it meets the requirements, and inspect the anti-corrosion coating as a whole. If there are defects such as leaks, re-coat it in time. After standing in a shaded and ventilated place for 7 days, confirm that there are no defects on the surface of the anti-corrosion coating before putting it into use.

[0153] The present invention takes the stainless steel plate before and after coating with the nanoparticle modified heavy anti-corrosion material of Example 1 as an example, and characterizes its macroscopic morphology respectively, and the results are as follows Figure 4 shown. Figure 4 In the figure, (a) is a photograph of a stainless steel plate before coating with the nanoparticle-modified heavy-duty anti-corrosion material of Example 1, and (b) is a photograph of a stainless steel plate after coating with the nanoparticle-modified heavy-duty anti-corrosion material of Example 1.

[0154] By comparison Figure 4 It can be seen from the test results of Figures (a) and (b) that the nanoparticle-modified heavy-duty anti-corrosion material of the present invention can form a uniform anti-corrosion coating on the surface of the stainless steel plate. In order to further verify the anti-corrosion performance of the nanoparticle-modified heavy-duty anti-corrosion material of the present invention as an anti-corrosion coating, the present invention also tested the performance of the anti-corrosion coating corresponding to Examples 1 to 3 formed according to the above method, and the test results are shown in Table 3.

[0155] Table 3 Performance indicators of the anti-corrosion coatings corresponding to Examples 1 to 3

[0156] By comparing the test results in Table 3 with those in Table 1 and Table 2, it can be seen that the performance indicators of the nanoparticle modified heavy-duty anticorrosion material of the present invention far exceed the technical level of existing anticorrosion materials and are suitable for high salt spray, high humidity and heat, high Cl - It is suitable for environments with high corrosion resistance and has excellent functional stability and anti-corrosion effect.

[0157] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

Claims

1. A nanoparticle modified heavy-duty anticorrosion material, characterized in that: The raw materials for its preparation are composed of the following components in mass percentage: Component A 60%~80%, component B 10%~25% and first solvent 10%~30%, totaling 100%; The raw materials for preparing component A are composed of the following components in percentage by mass: Resin solution 45%~60%, graphene oxide 0.5%~5%, polyaniline nanofiber 8%~20%, carbon nanotube 0.5%~5%, filler 0.6%~40%, additive 0.3%~3% and co-solvent 8%~12%, totaling 100%; The raw materials for preparing component B are composed of the following components in percentage by mass: Polyamide 40%~60% and second solvent 40%~60%, total 100%; The polyaniline nanofibers are prepared by the following steps: A layer of polyaniline is coated on the surface of the nano metal oxide by adopting a heteroelement ternary copolymerization emulsion polymerization method to form a core / shell structure with the nano metal oxide as the core and the polyaniline as the shell, thereby obtaining the polyaniline nanofiber; wherein the nano metal oxide is one or more of CeO2, ZnO2, TiO2, Al2O3 and Fe2O3.

2. The nanoparticle modified heavy-duty anticorrosive material according to claim 1, characterized in that: The resin solution is prepared by mixing the resin and the third solvent in a mass ratio of 2 to 5:1; Wherein, the third solvent is a mixed solution of xylene, cyclohexanone and n-butanol.

3. The nanoparticle modified heavy-duty anticorrosive material according to claim 1, characterized in that: The first solvent is a mixed solution of xylene, cyclohexanone and n-butanol; The second solvent is a mixed solution of xylene, cyclohexanone and n-butanol.

4. The nanoparticle modified heavy-duty anticorrosive material according to claim 1, characterized in that: The additive is one or both of a defoamer and a dispersant.

5. The nanoparticle modified heavy-duty anticorrosive material according to claim 1, characterized in that: The filler is one or more of talcum powder, calcite, lithopone and SiO2.

6. The nanoparticle modified heavy-duty anticorrosive material according to claim 1, characterized in that: The co-solvent is one or both of propylene glycol methyl ether and isopropyl alcohol.

7. A method for preparing the nanoparticle-modified heavy-duty anticorrosive material according to any one of claims 1 to 6, characterized in that: The following steps are involved: According to the mass percentage component composition of the raw materials prepared by the component A, the corresponding masses of resin solution, graphene oxide, polyaniline nanofibers, carbon nanotubes, fillers, additives and cosolvents are weighed respectively for use; the weighed graphene oxide, polyaniline nanofibers, carbon nanotubes, fillers, additives and cosolvents are sequentially dispersed in the weighed resin solution, and stirred evenly to obtain a first mixed material; the first mixed material is ball-milled to obtain a second mixed material; the second mixed material with a fineness of <10 μm is collected to obtain component A; According to the mass percentage composition of the raw materials prepared by the component B, weigh the corresponding mass of polyamide and the second solvent respectively for use; evenly disperse the weighed polyamide in the second solvent to obtain the component B; According to the mass percentage component composition of the raw material for preparing the nanoparticle modified heavy-duty anticorrosive material, weigh the corresponding mass of component A, component B and the first solvent respectively; After component A is left to stand, the component A is stirred and mixed with component B, and then the first solvent is added and stirred and mixed to obtain a third mixed material; After the third mixed material is left to stand for a static treatment, the nanoparticle-modified heavy-duty anti-corrosion material is obtained.

8. The method for preparing the nanoparticle-modified heavy-duty anticorrosive material according to claim 7, characterized in that: The ball milling rate of the ball milling treatment is 1000 rpm to 1500 rpm, and the ball milling time is 1.5 to 2.5 h.

9. Use of the nanoparticle-modified heavy-duty anti-corrosion material according to any one of claims 1 to 6 in the preparation of an anti-corrosion coating.

10. The use of the nanoparticle modified heavy anti-corrosion material according to claim 9 in the preparation of an anti-corrosion coating, characterized in that: The nanoparticle-modified heavy-duty anti-corrosion material is coated on the surface of the substrate to be anti-corroded by spraying, and after curing, an anti-corrosion coating is formed on the surface of the substrate to be anti-corroded; and the thickness of the anti-corrosion coating formed on the surface of the substrate to be anti-corroded is 100μm~700μm.

Citation Information

Patent Citations

  • Nanofiber heavy-duty anti-corrosive coating, preparation method and spraying method of nanofiber heavy-duty anti-corrosive coating

    CN102604509A

  • Anticorrosive and antirust nanometer fiber paint for containers, method for preparing and spraying paint

    CN102786861A

  • Efficient nanofiber solar energy absorption composite membrane as well as preparing and spraying method thereof

    CN103694877A

  • Polyaniline graphene nano composite anticorrosion paint and preparation method thereof

    CN104910752A

  • Graphene-epoxy composite anticorrosive coating and preparation method and application thereof

    CN108373746A

Cited By

  • Modified graphene oxide / polyaniline composite material and application thereof in water-based anticorrosive antistatic coating

    CN120173489A

  • High-corrosion-resistance coating and valve applying same

    CN122037635A